Determinants of CD4 Immune Recovery Among Individuals on Antiretroviral Therapy in South Africa : A National Analysis - World Bank (World Bank, Washington, DC, 2016)
This report presents the findings of a large national analysis of determinants of CD4 immune recovery among individuals on antiretroviral therapy in South Africa. It is part of the second phase of a series of analytical and evaluation studies contributing to the design of an impact and process evaluation of South Africa’s National Adherence Guidelines for Chronic Diseases. The analysis was conducted by the National Institute for Communicable Diseases (NICD) in collaboration with the National Health Laboratory Service (NHLS), Boston University/Health Economics and Epidemiology Research Office (HE2RO), the National Department of Health of South Africa, and the World Bank. The analysis used a novel database created through probabilistic matching of routine CD4 count and viral load data to unique individuals. The report describes the proportions of individuals 15 years or older who initiated antiretroviral therapy between 2010 and 2014 and achieved CD4 count recovery to 200, 350 and 500 cells/μl, their time to CD4 count recovery, and extent of recovery in the first 12 months of follow up. The cohort included 1,070,900 individuals (4.37 million CD4 tests). Findings suggest that among South African HIV patients under treatment, CD4 immune recovery is associated with age, sex, baseline CD4 count and viral suppression. Demographic CD4 recovery patterns can inform CD4 monitoring policies in resource-constrained settings.